Environmentally friendly low temperature resistant and crack-resistant concrete and preparation method thereof

By using special formulas such as crustacean exoskeleton powder, silica fume, recycled aggregate and glass fiber in concrete, the mechanical properties deterioration and cracking of ordinary concrete after freeze-thaw cycle are solved, and efficient freezing resistance and durability are improved, with environmental protection and sustainability advantages.

CN116332589BActive Publication Date: 2025-04-01CHINA RAILWAY 15TH BUREAU GROUP CORPORATION LIMITED +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310068582.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-06
Publication Date
2025-04-01
Estimated Expiration
2043-02-06

Smart Images

  • Figure BDA0004064038840000041
    Figure BDA0004064038840000041
  • Figure BDA0004064038840000051
    Figure BDA0004064038840000051
  • Figure BDA0004064038840000052
    Figure BDA0004064038840000052
Patent Text Reader

Abstract

The invention discloses an environment-friendly low-temperature resistant anti-cracking concrete, which is prepared from the following raw materials in parts by weight: 550-620 parts of cement; 55-90 parts of crustacean exoskeleton powder; 45-80 parts of silica fume; 615-650 parts of coarse aggregate; 400-435 parts of recycled medium aggregate; 200-235 parts of recycled fine aggregate; 10-45 parts of mixed glass fiber; 12-19 parts of water reducer; 210-245 parts of water; the particle size of the coarse aggregate is 5-15 mm and is continuously graded; the recycled medium aggregate is obtained by crushing waste concrete or waste bricks, and the particle size is 1-4 mm; the recycled fine aggregate is obtained by crushing waste concrete or waste bricks, and the particle size is 0.3-0.9 mm; the mixed glass fiber is obtained by mixing glass fibers with lengths of 2-4 mm, 6-8 mm and 13-17 mm in a mass ratio of 1:0.5-1.5:0.5-1.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete materials, and in particular to an environmentally friendly low-temperature resistant and crack-resistant concrete and a preparation method thereof. Background Art

[0002] As a hard building material, concrete is made of cementitious materials (usually Portland cement, also known as ordinary cement or silicate cement) and mineral aggregates (such as washed sand and gravel or crushed stone) mixed with enough water to solidify and bind the cement. With the rapid development of the construction industry, the freeze-thaw damage problem of building structures in cold regions has become increasingly prominent. The mechanical properties of ordinary concrete will seriously deteriorate after being subjected to freeze-thaw cycles, and with the long-term effect of loads, the concrete in the building structure is prone to cracking. The large-scale use of concrete in building structures and the excessive exploitation of raw materials such as stone have also caused serious environmental problems. Summary of the invention

[0003] The purpose of the present invention is to provide an environmentally friendly low-temperature resistant and crack-resistant concrete in view of the above problems. This concrete is green and environmentally friendly and can withstand low temperatures and has excellent crack resistance.

[0004] In order to achieve its purpose, the present invention adopts the following technical solution:

[0005] An environmentally friendly low-temperature resistant and crack-resistant concrete is prepared from the following raw materials in parts by weight:

[0006] 550-620 parts of cement; 55-90 parts of crustacean exoskeleton powder; 45-80 parts of silica fume; 615-650 parts of coarse aggregate; 400-435 parts of recycled medium aggregate; 200-235 parts of recycled fine aggregate; 10-45 parts of mixed glass fiber; 12-19 parts of water reducer; 210-245 parts of water;

[0007] The particle size of the coarse aggregate is continuously graded from 5 to 15 mm;

[0008] The recycled aggregate is obtained by crushing waste concrete or waste bricks, and the particle size is 1-4 mm;

[0009] The recycled fine aggregate is obtained by crushing waste concrete or waste bricks, and has a particle size of 0.3-0.9 mm;

[0010] The mixed glass fibers are obtained by mixing glass fibers with lengths of 2-4 mm, 6-8 mm, and 13-17 mm in a mass ratio of 1:0.5-1.5:0.5-1.5.

[0011] Preferably, the above concrete is prepared from the following raw materials in parts by weight:

[0012] 550-580 parts of cement; 75-90 parts of crustacean exoskeleton powder; 65-80 parts of silica fume; 635-650 parts of coarse aggregate; 400-415 parts of recycled medium aggregate; 200-215 parts of recycled fine aggregate; 10-25 parts of mixed glass fiber; 16-19 parts of water reducer; 210-225 parts of water.

[0013] Preferably, the above concrete is prepared from the following raw materials in parts by weight:

[0014] 590-620 parts of cement; 55-70 parts of crustacean exoskeleton powder; 45-60 parts of silica fume; 615-630 parts of coarse aggregate; 420-435 parts of recycled medium aggregate; 220-235 parts of recycled fine aggregate; 30-45 parts of mixed glass fiber; 12-15 parts of water reducer; 230-245 parts of water.

[0015] Preferably, the above concrete is prepared from the following raw materials in parts by weight:

[0016] 590-610 parts of cement; 60-70 parts of crustacean exoskeleton powder; 50-60 parts of silica fume; 620-630 parts of coarse aggregate; 420-430 parts of recycled medium aggregate; 220-230 parts of recycled fine aggregate; 30-40 parts of mixed glass fiber; 13-15 parts of water reducer; 230-240 parts of water.

[0017] Preferably, the exoskeleton of the crustacean is a shell, a crab shell, or a shrimp shell; the shell includes an oyster shell, a snail shell, a scallop shell, or a clam shell; and the exoskeleton powder of the crustacean is a micron-grade powder, preferably with a particle size of 20-50 microns.

[0018] Preferably, the cement is silicate cement, the coarse aggregate is selected from limestone, pebble, and granite, the silica fume particle size is 0.15-0.2 microns, and the glass fiber is alkali-free chopped fiber.

[0019] Preferably, the mixed glass fiber is formed by mixing glass fibers with lengths of 2.5-3.5 mm, 6-7 mm, and 14-16 mm in a mass ratio of 1:0.8-1.2:0.8-1.2 or 1:0.9-1.1:0.9-1.1.

[0020] Another object of the present invention is to provide a method for preparing the concrete described in any one of the above items, wherein the raw materials are mixed according to a mass ratio, water is added, stirred evenly, and the concrete is obtained by curing.

[0021] Preferably, the method comprises the following steps:

[0022] Step 1: Weigh the water reducer and water, and stir them thoroughly for 4-6 minutes to obtain a primary mixed solution;

[0023] Step 2: adding the crustacean exoskeleton powder to the primary mixed solution obtained in step 1, and stirring for 3-5 minutes to obtain a secondary mixed solution;

[0024] Step 3: Add cement, silica fume, coarse aggregate, recycled medium aggregate, recycled fine aggregate and mixed glass fiber into a mixer, stir for 6-8 minutes until evenly mixed, then add the secondary mixture and continue stirring for 18-22 minutes;

[0025] Step 4: After stirring, take it out and put it into a mold to vibrate and compact it. After it is formed at room temperature, remove the mold and then take it out after standard curing.

[0026] The beneficial effects of the present invention are:

[0027] 1. The present invention adds silica fume as an admixture to concrete, which can improve the workability of concrete and improve its load resistance and frost resistance by filling small pores in concrete. The powder made from discarded crustacean exoskeletons is also added to concrete as an admixture, which can not only increase the degree of hydration reaction between silica fume and cement, induce the production of CSH gel, and make the connection area between recycled aggregate and cement paste tighter, but also further fill large and medium pores inside concrete, inhibit moisture from entering the concrete under severe cold conditions, and prevent freeze-thaw damage to concrete due to moisture frost heaving. The exoskeleton powder of crustaceans combined with silica fume has a positive synergistic effect on the frost resistance and durability of concrete.

[0028] 2. The present invention uses crushed waste concrete / waste bricks as recycled medium aggregate and recycled fine aggregate, which saves resources and achieves green environmental protection. In addition, the aggregates used are divided into coarse, medium and fine aggregates, with continuous grading, which optimizes the internal pore structure of concrete and is conducive to improving its mechanical properties and frost resistance.

[0029] 3. The present invention adds glass fiber filaments of different lengths into concrete. Glass fiber is lighter than ordinary steel fiber and cheaper than carbon fiber. Moreover, glass fibers of different lengths can be dispersed and three-dimensionally distributed in concrete, and bond with the internal structure of concrete to form a strong pulling effect. For example, in an embodiment of the present invention, 3mm and 6mm glass fibers are mainly used to form a dense grid structure to inhibit the generation of micro cracks in the early stage of loading; and 15mm glass fibers are mainly used to delay the further extension and expansion of cracks under long-term loading of concrete. The simultaneous addition of glass fibers of different lengths into concrete greatly improves the crack resistance of environmentally friendly concrete under long-term load. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited thereto.

[0031] The experimental methods in the following examples are all conventional methods unless otherwise specified; the materials used are all conventional materials in the art and can be obtained commercially unless otherwise specified.

[0032] Example 1

[0033] The main raw materials used in the embodiments of the present invention are as follows:

[0034] The cement used is P·O42.5R ordinary Portland cement, with a relative density of 3.62g / cm 3 , with a specific surface area of ​​358m 2 / kg, initial setting time ≥150min, final setting time ≤240min.

[0035] The exoskeleton powder of crustaceans is made of lobster shell powder or crab shell powder. The lobster shells or crab shells discarded by people after eating are cleaned and disinfected, baked and dried in an oven at a temperature of 140-150℃, and finally ground into fine powder with a particle size of 20-50 microns. The particle size of silica fume is 0.15-0.2 microns, and the specific surface area is 21-23m 2 / g, lobster shell powder and silica fume are mixed and added to concrete as external admixtures. Examples 1-6 and Comparative Examples 3-7 use lobster shell powder, and Examples 7-8 use crab shell powder.

[0036] The coarse aggregate is limestone crushed stone with a particle size of 5-15mm and a crushing index of 4.5%.

[0037] The recycled medium aggregate is obtained by crushing and screening waste concrete or waste bricks with a crusher, and the particle size of the crushed waste concrete is controlled at 1-4mm. The recycled fine aggregate is obtained by crushing and screening waste concrete or waste bricks with a crusher, and the particle size of the crushed waste bricks is controlled at 0.3-0.9mm. The waste bricks can be waste bricks generated in production and life, such as shale bricks, coal gangue bricks, and lime sand bricks. The waste shale bricks are used in this embodiment. The recycled medium aggregate in Examples 1-6 and Comparative Examples 1-7 is obtained by crushing waste concrete, and the recycled fine aggregate is obtained by crushing waste bricks; the recycled medium aggregate in Examples 7-8 is obtained by crushing waste bricks, and the recycled fine aggregate is obtained by crushing waste concrete.

[0038] The type of glass fiber used is alkali-free chopped fiber with a single filament diameter of 10-15 μm. The mixed glass fibers in Examples 1 and 5-8 are composed of wear-resistant and crack-resistant glass fibers of 3 mm, 6 mm, and 15 mm in length mixed in equal weight ratios, the mixed glass fibers in Example 2 are composed of wear-resistant and crack-resistant glass fibers of 3 mm, 6 mm, and 15 mm in length mixed in a weight ratio of 1:0.5:1.5, the mixed glass fibers in Example 3 are composed of wear-resistant and crack-resistant glass fibers of 3 mm, 6 mm, and 15 mm in length mixed in a weight ratio of 1:1:0.5, and the mixed glass fibers in Example 4 are composed of wear-resistant and crack-resistant glass fibers of 3 mm, 6 mm, and 15 mm in length mixed in a weight ratio of 1:1.5:1.5.

[0039] The water reducing agent is naphthalene fine water reducing agent with a water reducing efficiency of 25% and a brown-yellow appearance.

[0040] The water is ordinary tap water.

[0041] The concrete of this embodiment is prepared by using the above raw materials according to the following steps:

[0042] Step 1: Weigh the water reducer and water, and stir them thoroughly for 4-6 minutes to obtain a primary mixed solution;

[0043] Step 2: adding the crustacean exoskeleton powder to the primary mixed solution obtained in step 1, and stirring for 3-5 minutes to obtain a secondary mixed solution;

[0044] Step 3: Add cement, silica fume, coarse aggregate, recycled medium aggregate, recycled fine aggregate and mixed glass fiber into a mixer, stir for 6-8 minutes until evenly mixed, then add the secondary mixture and continue stirring for 18-22 minutes;

[0045] Step 4: After stirring, take it out and put it into a mold to vibrate and compact it. After it is formed at room temperature, remove the mold and then take it out after standard curing.

[0046] The concrete materials in Table 1 were prepared according to the above method. The specific formula of each experimental group is shown in Table 1 (the values ​​in Table 1 are parts by weight):

[0047] Table 1

[0048]

[0049]

[0050] Compared with Example 1, Comparative Example 5 differs in that: the chopped glass fiber strands with a length of 3 mm are removed from the mixed glass fiber; the rest are the same as Example 1. Compared with Example 1, Comparative Example 6 differs in that: the chopped glass fiber strands with a length of 6 mm are removed from the mixed glass fiber; the rest are the same as Example 1. Compared with Example 1, Comparative Example 7 differs in that: only the chopped glass fiber strands with a length of 15 mm are retained in the mixed glass fiber; the rest are the same as Example 1.

[0051] The performance of the concrete materials in Table 1 was tested:

[0052] Split tensile strength: refer to GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" to make standard test blocks, and measure the splitting tensile strength of standard test blocks after curing for 7d, 14d and 28d;

[0053] Antifreeze performance test: refer to GB / T50082-2009 "Standard for test methods for long-term performance and durability of ordinary concrete" to make standard test blocks, use the quick freezing method to test, and evaluate the antifreeze performance through the maximum number of freeze-thaw cycles.

[0054] The test results are shown in Table 2.

[0055] Table 2

[0056]

[0057]

[0058] The test results in Table 2 show that the 7d splitting tensile strength, 14d splitting tensile strength, 28d splitting tensile strength and maximum freeze-thaw cycle number of the concrete of Examples 1-8 are better than those of Comparative Examples 1-7, and the frost resistance grades of Examples 1-8 are all above F300, while the frost resistance grades of Comparative Examples 1-7 are all below F300. The environmentally friendly low-temperature resistant anti-cracking concrete prepared in Examples 1-8 has excellent crack resistance and frost resistance, and has a good application prospect; while the concrete prepared in Comparative Examples 1-7 has poor crack resistance and frost resistance, and is not suitable for application in actual engineering.

[0059] By comparing the performance test data of Examples 1-8, it can be seen that different amounts of raw materials affect the mechanical properties and frost resistance of concrete. The splitting tensile strength and frost resistance of Examples 5-8 are better than those of Examples 1-4, and the concrete splitting tensile strength and frost resistance of Example 6 are the best.

[0060] In Comparative Example 1, no lobster shell powder was added. Compared with Example 1, the degree of hydration reaction of cement and silica fume decreased, the internal porosity increased after curing for different days, and external moisture easily entered the concrete, resulting in reduced splitting tensile strength and frost resistance.

[0061] In Comparative Example 2, the lobster shell powder was replaced with an equal amount of fly ash. Compared with Example 1, the mechanical properties and the maximum freeze-thaw cycle number of the environmentally friendly concrete were reduced to a certain extent, indicating that the lobster shell powder as an admixture is better than fly ash in improving the splitting tensile strength and frost resistance of concrete.

[0062] In Comparative Example 3, no silica fume is added, the fluidity of the concrete is reduced in the initial mixing stage, the workability is reduced, the splitting tensile strength under different curing days is poorer than that of Example 1, and the frost resistance is also greatly weakened.

[0063] In the raw materials of Comparative Example 4, the recycled medium aggregate is replaced with an equal amount of coarse aggregate. Compared with Example 1, the increase in the amount of large-particle aggregate increases the internal porosity of the concrete and reduces the density of the concrete, resulting in reduced mechanical properties and frost resistance.

[0064] In the mixed glass fiber of Comparative Example 5, chopped glass fiber filaments with a length of 3 mm were removed, in the mixed glass fiber of Comparative Example 6, chopped glass fiber filaments with a length of 6 mm were removed, and in the mixed glass fiber of Comparative Example 7, only chopped glass fiber filaments with a length of 15 mm were retained. Compared with Example 1, the splitting tensile strength after curing for different days was greatly reduced, indicating that compared with glass fiber filaments of a single length or two lengths, the mixed glass fiber in the embodiment has the strongest tensile effect on the internal structure of concrete after being added to the concrete, and has the best effect on improving the tensile properties of environmentally friendly concrete.

Claims

1. An environmentally friendly low temperature resistant and crack resistant concrete, characterized in that: It is prepared from the following raw materials in parts by weight: 590-620 parts of cement; 55-70 parts of crustacean exoskeleton powder; 45-60 parts of silica fume; 615-630 parts of coarse aggregate; 420-435 parts of recycled medium aggregate; 220-235 parts of recycled fine aggregate; 30-45 parts of mixed glass fiber; 12-15 parts of water reducer; 230-245 parts of water; the cement is silicate cement; The coarse aggregate is selected from limestone, pebble, and granite, and the particle size of the coarse aggregate is 5-15 mm in continuous grading; The recycled aggregate is obtained by crushing waste concrete or waste bricks, and the particle size is 1-4 mm; The recycled fine aggregate is obtained by crushing waste concrete or waste bricks, and has a particle size of 0.3-0.9 mm; The mixed glass fiber is obtained by mixing glass fibers with lengths of 2-4 mm, 6-8 mm, and 13-17 mm in a mass ratio of 1: 0.5-1.5: 0.5-1.

5.

2. The concrete according to claim 1, characterized in that: It is prepared from the following raw materials in parts by weight: 590-610 parts of cement; 60-70 parts of crustacean exoskeleton powder; 50-60 parts of silica fume; 620-630 parts of coarse aggregate; 420-430 parts of recycled medium aggregate; 220-230 parts of recycled fine aggregate; 30-40 parts of mixed glass fiber; 13-15 parts of water reducer; 230-240 parts of water.

3. The concrete according to claim 1 or 2, characterized in that: The exoskeleton of the crustacean is a shell, a crab shell, or a shrimp shell; the shell includes an oyster shell, a snail shell, a scallop shell, or a clam shell; and the exoskeleton powder of the crustacean is a micron-grade powder with a particle size of 20-50 microns.

4. The concrete according to claim 1, characterized in that: The silica fume particle size is 0.15-0.2 microns, and the glass fiber is alkali-free chopped fiber.

5. The concrete according to claim 1, characterized in that: The mixed glass fiber is formed by mixing glass fibers with lengths of 2.5-3.5 mm, 6-7 mm, and 14-16 mm in a mass ratio of 1:0.8-1.2:0.8-1.

2.

6. The method for preparing concrete according to any one of claims 1 to 5, characterized in that: The raw materials are mixed according to a mass ratio, water is added, stirred evenly, and cured to obtain the concrete.

7. The method according to claim 6, characterized in that The steps include: Step 1: Weigh the water reducer and water, and stir them thoroughly for 4-6 minutes to obtain a primary mixed solution; Step 2: adding the crustacean exoskeleton powder to the primary mixed solution obtained in step 1, and stirring for 3-5 minutes to obtain a secondary mixed solution; Step 3: Add cement, silica fume, coarse aggregate, recycled medium aggregate, recycled fine aggregate and mixed glass fiber into a mixer, stir for 6-8 minutes until evenly mixed, then add the secondary mixture and continue stirring for 18-22 minutes; Step 4: After stirring, take it out and put it into a mold to vibrate and compact it. After it is formed at room temperature, remove the mold and then take it out after standard curing.

Citation Information

Patent Citations

  • Preparation method of durable type anti-freezing concrete

    CN108298906A

  • Preparation technology of high-elastic modulus fiber self-stress recycled concrete

    CN109369121A